Pemikiran K.H Ahmad Dahlan dan K.H Hasyim Asy'ari dalam Bidang Pendidikan - Rahmah Rahmah (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2021)
The results of the incredible thoughts of K.H Ahmad Dahlan have influenced on the history of the world of education in Indonesia, especially in the field of Islamic Education. Islamic education has a major role in determining the fate of the nation. This state of affairs made him think and reflect while looking for a solution. His ideals is through the Islamic religious education, he will be able to give birth to the new man, who is able to perform as an intellect scholar that is a Muslim who has the determination and knowledge as well as strong physically and spiritually. In actualizing his ideal, K.H Ahmad Dahlan (the founder of Muhammadiyah) had combined the two systems of philosophy of education. In order to prevail the systems, he performed two actions at once namely giving religious instruction in the Dutch school which was secular and setting up schools where religious instruction and general lessons are equally taught. K.H Hasyim asy'ari is a figure of scholars that contributes to the development of science in Indonesia. His thinking is emphasized on a concept of education which discusses ethics in the search for knowledge. Demanding science is the work of religion so that all people who seek it should pay attention to ethics. In the search for knowledge and religious activities, both of which must be accompanied gentlemanly behavior of al-akhlaqul karimah.